Las relaciones bilaterales entre Argentina y Estados Unidos desde el retorno a la democracia. (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
Historically, foreign relations between Argentina and the United States (USA) have been complicated, going through moments of high conflict and others of exacerbated harmony. Throughout the 36 years that this article involves, various internal and external factors had a more or less decisive influence, depending on the case, in the bilateral relations of both countries. In this paper, an attempt will be made to account for such factors in order to analyze the continuities or ruptures that have arisen and that hampered the construction of a public policy in matters of foreign policy.
Keywords: Argentina; United States; Foreign Policy; Public Politics